Keterbatasan Fasilitas Pembelajaran dan Dampaknya terhadap Kinerja Guru Sekolah Dasar - Krisna S. Latip; Moh. Rehan N. Gante; Fazrian Samarati; Wulan Nurcahyani; Sasta Imran (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2026)
This study aims to analyze the limitations of learning facilities and their impact on elementary school teachers’ performance. A qualitative descriptive approach was employed at SDN 1 Telaga and SDN 4 Telaga, Gorontalo Regency. Data were collected through observation, in-depth interviews, and documentation. The findings reveal significant differences in the availability of technology-based learning facilities. Adequate facilities support more varied and interactive learning, while limited facilities restrict instructional media and teaching strategies. It is concluded that learning facilities support teacher performance, although teacher competence and commitment remain the main determinants of effective learning.